Keanekaragaman Makrofauna Tanah pada Pertanaman Kacang Nagara dengan Aplikasi Mulsa Eceng Gondok - Aphrodyanti, Lyswiana; Mika, Mika; Apriani, Rila Rahma; Mulyawan, Ronny; Rizqiana, Sista; Ellya, Hikma (Universitas Muhammadiyah Mataram, 2024)
Nagara cowpea is a local crop from South Kalimantan that is grown on swampland. However, nagara cowpea cultivation on swamp land can only be planted once a year, in the dry season. It can be planted more than once a year if it is re-adapted to dry land by providing organic material in the form of water hyacinth mulch and identifying the diversity of soil macrofauna. The purpose of this study was to determine the diversity of soil macrofauna in each treatment of water hyacinth mulch. This study used descriptive exploration method. Soil macrofauna samples were taken by purposive sampling in cowpea raisebeds that were applied water hyacinth mulch. Furthermore, identification and calculation of the number of soil macrofauna were carried out in the laboratory. Data were analyzed quantitatively in tables to explain differences in diversity, evenness, and dominance. The results showed that the diversity of soil macrofauna in the three treatments had a medium index value. Individual richness of soil macrofauna in the three treatments has a low index value. Evenness of soil macrofauna has a value of more than 0.6 which indicates that the distribution of individuals per species is evenly distributed. This is in accordance with the dominance value of macrofauna, that there is no dominant species.